Esterification and In silico analysis of lipase catalyzed synthesis of flavour ester - Mohamed Rais, Nor Nadirah (2015)
Flavour esters can be made artificially from the reaction between alcohols and carboxylic acids and this reaction is called esterification. Flavour refers to the combination of taste, touch and smell. Eighty percent (80%) of taste comes from smell. Esters have the ability to produce artificial fruit aromas. In this work, strawberry (ethyl hexanoate), banana (isoamyl acetate) and pear (propyl acetate) aromas are produced by esterification process, catalysed by the cold adapted Lipase AMS8. Esterification using cold adapted enzymes are not well studied. The use of cold active lipase would provide more advantages and economic benefits to the industry. Analysis using FT-IR and GC-MS showed the presence of esters at IR spectrum of ethyl hexanoate, isoamyl acetate and propyl acetate at 1704.30, 1706.25 and 1701.26 cm-1 respectively and the mass spectrum 144, 130 and 102 m/z respectively. Esterification reaction in the presence of toluene as an organic solvent showed higher ester conversions (ethyl hexanoate: 53.13%, isoamyl acetate: 50.77% and propyl acetate: 20.92%). In the absence of organic solvents, ester conversion has a lower yield (ethyl hexanoate: 29.45%, isoamyl acetate: 22.43% and propyl acetate: 10.05%). To support the experimental data, computational analysis was done via experimented docking between Lipase AMS8 and ligands which were toluene, hexanoic acid and ethanol. It showed multiple interactions between the lid and active sites of Lipase AMS8.